Effects of four weeks of physical exercise in water on the severity of low back pain in pregnant women with previous history of pregnancy low back pain: a randomized controlled clinical trial - Behrooz Nazari; Abbasali Dorosti; Farhad Mirzaei (Mashhad University of Medical Sciences, 2020)
Introduction: Given the high prevalence of low back pain in pregnancy and the increase in pain intensity in women with a history of low back pain in previous pregnancies and the recommendation of not to use analgesics in pregnancy, this study was performed with aim to investigate the effect of four weeks of physical exercise in water on the severity of low back pain in pregnant women with previous history of pregnancy low back pain. Methods: This randomized controlled clinical trial study was conducted with participation of 80 pregnant women with pregnancy low back pain and previous history of pregnancy low back pain at Tabriz University of Medical Sciences in 2019. In addition to lifestyle modification, the intervention group performed stretching and strengthening exercises for 16 session of 1 hour in the water, and the control group was only encouraged to improve their lifestyle. The Qubak questionnaire and demographic information were used before and after the intervention for all participants. Data was analyzed by SPSS software (version 20) and Clomogrov-Smirnov and dependent T-test. P <0.05 was considered statistically significant. Results: At the end of the intervention, the intensity of pain in the intervention group (23.45±03.56) was significantly lower than the control group (77.15±13.03) (P=0.001); on the other hand, in the intervention group, the intensity of pain at the end of the study (23.45±03.56) was significantly reduced compared to the beginning of the study (73.19±11.42) (P=0.001). While in the control group, no significant changes occur after the intervention (77.15±13.03) compared to before it (74.36±12.23) (P=0.419). Conclusion: Four weeks of physical exercise in the water could reduce the severity of low back pain in pregnant women with a history of low back pain; these movements are recommended for pregnant women.